The leafhopper genus Atkinsoniella Distant (Hemiptera: Cicadellidae: Cicadellinae) with descriptions of two new species from China - Feng, Ling; Zhang, Yalin (Zootaxa, 2015)
Two new species in the genus Atkinsoniella from China, Atkinsoniella longiuscula, and A. valida spp. nov. are described and illustrated. A checklist of the known species worldwide is provided.